Suggestions for an archaeologist: a side note to “Fellini-Satyricon. L’immaginario dell’antico” (LANX. Journal of the Scuola di Specializzazione in Beni Archeologici - Università degli Studi di Milano, 2010)
A reflection on Fellini’s creativity and his archaeological knowledge of the Vesuvian sites (Pompeii, and, especially, Herculaneum); the text was inspired by the reading of the book Fellini-Satyricon. L’immaginario dell’antico (a cura di F. Slavazzi, E. Gagetti, R. De Berti), which was presented in Milan on May 10, 2010.
Keywords: Fellini; PompeiIi; Herculaneum; cinema; Satyricon; archaeology; immaginario dell’antico